Self-assessment at the Pedro Ruiz Gallo National University, a need to achieve quality education – Lambayeque 2014 - Piscoya Tejada, Juan Fernando (2015)
Self-assessment is the most important aspect of a university regulation .This document is considered as a process of analysis and reflection to promote the change for the betterment of the University according to its goals and objectives based on a set of criteria and standards also set by the institution itself. Moreover, accreditation is described as the measure that should be complemented with organizational changes and efficiency of study programs, which of course vary with the advancement of knowledge. Also, the results of evaluation of institutional management are presented in a Supplemental Educational Program of the Social Science History and Education Faculty at Pedro Ruiz Gallo National University, as well as the trend in vocational training and self-assessment of quality management is implemented in the Complementation Program. In addition, a self-assessment process for the Complementation Pedagogical Program- FACHSE - UNPRG is proposed to assume the contributions the theory of conscious processes of Carlos Alvarez de Zayas.